A field guide to spiders of Australia - Whyte, Robert 1955-; Anderson, Greg 1958- (CSIRO Publishing, 2017)
Australians have a love-hate relationship with spiders. Spiders inspire fear, especially dangerous species such as the Redback and Sydney Funnelweb. Yet, Peacock Spiders, whose males spread a colourful fan and wave their legs in a courtship dance to impress females, have won rapturous appreciation worldwide. A Field Guide to Spiders of Australia uses photographs of live animals to enable identification of commonly encountered spiders to the family level and, in some cases, to genus and species. Featuring over 1300 colour photographs, it is the most comprehensive account of Australian spiders ever published. With more than two-thirds of Australian spiders yet to be scientifically described, this book sets the scene for future explorations of our extraordinary Australian fauna....